1991
DOI: 10.2307/3808986
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Mortality of Red-Cockaded Woodpecker Cavity Trees

Abstract: Over a 13-year period we examined the mortality of cavity trees (n = 453) used by red-cockaded woodpeckers (Picoides borealis) on national forests in eastern Texas. Bark beetles (53%), wind snap (30%), and fire (7%) were the major causes of cavity tree mortality. Bark beetles were the major cause of mortality in loblolly (Pinus taeda) and shortleaf (P. echinata) pines, whereas fire was the major cause in longleaf pines (P. palustris). Cavity trees on the Angelina National Forest (NF) were dying at a higher rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…forests in Georgia, USA, where the cause of death of half of the dead trees could not be determined. In a study of dead cavity trees in Texas, USA, Conner et al (1991) reported a similar proportion of 'unknown causes' of tree mortality.…”
Section: Discussionmentioning
confidence: 85%
“…forests in Georgia, USA, where the cause of death of half of the dead trees could not be determined. In a study of dead cavity trees in Texas, USA, Conner et al (1991) reported a similar proportion of 'unknown causes' of tree mortality.…”
Section: Discussionmentioning
confidence: 85%
“…SPB-induced pine tree deaths may trigger a series of ecological changes (e.g., Conner et al 1991Conner et al , 1998. The SPBrelated tree deaths cause openings in the forest canopy that permit increased light availability in the understory.…”
Section: Ecological Impacts and Environmental Damagementioning
confidence: 99%
“…is the major cause of RCW cavity tree loss in Texas loblolly and shortleaf pine stands in Texas , Kulhavy et al 1992. Trees favored by the RCW for nesting and roosting cavities tend to be old, ranging from approximately 60 to 130 years of age in loblolly and shortleaf pine, with slow radial growth, and infection with red-heart rot (Phellinus pini) (Conner and Locke 1982, Conner and O'Halloran 1987, Rudolph and Conner 1991. Such characteristics tend to place pine trees at high risk of attack by southern pine beetles and other phloemboring beetles, even when bark beetle populations are generally at endemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…The RCW normally excavates cavities totally in heartwood and prefers redheart (PheEZinus pini) heartwood infected trees for easier cavity excavation (Jackson 1977, Conner and Locke 1982, Hooper et al 1991.…”
Section: Introductionmentioning
confidence: 99%